Augmenter of Liver Regeneration Protein: A Promising Therapeutic Target for Hepatocellular Carcinoma - Katare, Deepshikha Pande (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Hepatocellular carcinoma (HCC), a deadly cancer form associated with poor prognosis and survival rate represents 5% new patients diagnosed every year worldwide. Despite significant research in the diagnostic, prognostic and therapeutic areas of HCC, no specific validated biomarkers or therapy are available for diagnosis and control the recurrence rate. Augmenter of liver is highly expressed during cirrhosis and has the ability to reduce migration cancerous hepatic cells, hence may have antimetastasis properties. Therefore, it potentiates to become a promising marker for HCC diagnosis as well as the therapeutic target. Materials and Methods: Animal model of hepato tumorigenesis was developed using Diethylnitrosamine and 2-Acetylaminofluorene. Biochemical and histopathological examinations were performed to study the disease progression. Furthermore, signature protein was identified using 2 DE gel and matrix-assisted laser desorption/ionization-time-of-flight/mass spectrometry. Docking studies were performed using iGEMDOCK9 for the best binding herbal compound to augmenter of liver regeneration (ALR) for future therapeutic uses. Results: Differentially expressed proteins between control and diseased rats were analyzed and one upregulated protein flavin adenine dinucleotide (FAD)-linked sulfhydryl oxidase ALR of 22.8 kDa was found to be present in HCC progression during cirrhosis. Conclusions: The present work is a success story with the marker discovery for the prognosis of HCC. This study reports the development of an animal model of liver cancer and systematic screening of protein-based marker FAD-linked Sulfhydryl Oxidase (ALR) with the disease progression. In future, it can be targeted for diagnosis of HCC and therapeutic approach as well.